PERAN FLEKSIBILITAS KERJA, KOMPENSASI DAN PUNISHMENT TERHADAP RETENSI KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA CV BERKAT SEJAHTERA SITUBONDO - Achmad Anas; Siti Soeliha; Riska Ayu Pramesthi (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
Employee retention has an important role in maintaining company stability and sustainability. Companies that are able to retain employees tend to have better operational continuity, lower recruitment costs, and a more productive work environment. Therefore, understanding the factors that influence employee retention is essential for organizational success. This research was conducted to analyze the effect of work disruption, compensation, and punishment on employee retention through job satisfaction as an intervening variable at CV Berkat Sejahtera Situbondo. This study employed a quantitative research approach using a saturated sampling technique, in which all employees of the company were involved as research respondents. Data were collected through questionnaires and analyzed using the Structural Equation Model–Partial Least Square (PLS-SEM) method with the assistance of SmartPLS 3.0 software. The use of this method was intended to examine both direct and indirect relationships among the variables studied. The results indicate that work disruption and compensation have a positive but insignificant effect on job satisfaction. Meanwhile, punishment shows a negative and insignificant influence on job satisfaction. Furthermore, work flexibility has a positive and significant effect on employee retention, indicating that flexible working conditions contribute to employees’ willingness to remain in the company. On the other hand, compensation and punishment have positive but insignificant effects on employee retention. Job satisfaction also demonstrates a negative and insignificant influence on employee retention. In addition, the findings reveal that job satisfaction is unable to mediate the relationship between work disruption, compensation, and punishment on employee retention. These results suggest that employee retention at CV Berkat Sejahtera Situbondo is influenced more directly by work flexibility than by job satisfaction. The study is expected to provide useful insights for management in formulating human resource policies aimed at improving employee retention.